2020
DOI: 10.1097/jom.0000000000001769
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Function Impairment After Acute Vibration Exposure

Abstract: Objective: This study was to investigate the acute effects of hand-arm vibrations on the nerve functions of the hands, and the impact of the grip force applied to the vibrating tool during exposure. Methods: Grip strength and perception of vibration, touch, and temperature were evaluated using quantitative sensory testing (QST) before and after vibration exposure in 21 occupationally unexposed individuals. The procedure was performed twice, with a highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Lofgren [20] experimented with variations to grip force and assessment of TTS of VPT. The results demonstrated that as the grip force increased, the tool vibration value decreased and the TTS value increased.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Lofgren [20] experimented with variations to grip force and assessment of TTS of VPT. The results demonstrated that as the grip force increased, the tool vibration value decreased and the TTS value increased.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The application of force during vibration exposure also affects the shift in the VPT. With the increase in force, the change in VPT follows an upward trend, similarly to the effect of the vibration level [8,12], suggesting that hand force may create a negative impact on hand sensorineural function. A similar influence of hand force on blood circulation during vibration was found in previous studies [16].…”
Section: Discussionmentioning
confidence: 82%
“…Among the existing research methods, the measurement of the vibrotactile perception threshold (VPT) has been proposed as a useful technique for screening and diagnosis as it corresponds to the HAV-induced nerve damage that occurs at a relatively early stage [5][6][7]. In addition, the acute response to vibration exposure could be detected by a temporary shift in the VPT, which was found to be sensitive to the vibrating intensity [8,9]. Apart from the vibration of the tool, the applied force and its impact is another important consideration in exposure assessment.…”
Section: Introductionmentioning
confidence: 99%
“…A control group was obtained from Löfgren et al [31], which consisted of male workers from the Department of Occupational and Environmental Medicine, Örebro University Hospital. Eight values and results from Quantitative Sensory Testing (QST) could be extracted from their study baseline characteristics.…”
Section: Study Design and Populationmentioning
confidence: 99%